An Integrated Fuzzy Multi-Criteria Decision Making Method For Supplier Evaluation - Ng, Peh Sang (2014)
This research investigates the risk exposure arising from the supplier evaluation criteria of cost, quality, delivery, and flexibility of the supplier. Penyelidikan ini bertujuan untuk mengkaji risiko yang timbul daripada kos, kualiti, penghantaran dan fleksibiliti bagi penilaian pembekal.